Simulation and experimental analysis of rotor-bearing system with rolling element bearing fault in axial piston pump under churning condition. (March 2023) - Wu, ZhuJin; Tang, Hesheng; Li, Yiming; Ren, Yan; Chen, Lei; Kumar, Anil
Axial piston pumps have been widely studied and applied in engineering applications. Generally, traditional simulation models are established to analyze the vibration characteristics of the pump without the churning effect of the gap annular flow. A new vibration model of a rotor-bearing system considering the oil churning effect and time-varying excitation introduced by localized faults on the rolling element bearing is proposed in this work. External forces on rotor-bearing system are solved to obtain time-varying displacement and contact stiffness coefficient based on lump mass method. The dynamic model has constructed to analyze the dynamic characteristics of rotor-bearing system with bearing faults. The validity of the model is verified by comparing the simulation results with the analysis results and the experimental results. The findings reveal that rolling element bearing with localized faults alters the vibration characteristics of the rotor-bearing system. Both the simulation results and the experimental results show the fault characteristic frequency of the rotor-bearing system and the explicit component of its harmonics. The fault characteristic frequency of rotor-bearing system with bearing faults is consistent with the simulation result, and the error is less than 10%. The spectrum of the experimental and simulated signals is similar and indicates the validity of the dynamical model.